2014
DOI: 10.1089/brain.2013.0187
|View full text |Cite
|
Sign up to set email alerts
|

Brain Topological Correlates of Motor Performance Changes After Repetitive Transcranial Magnetic Stimulation

Abstract: Repetitive transcranial magnetic stimulation (rTMS) influences the brain temporally beyond the stimulation period and spatially beyond the stimulation site. Application of rTMS over the primary motor cortex (M1) has been shown to lead to plastic changes in interregional connectivity over the motor system as well as alterations in motor performance. With a sequential combination of rTMS over the M1 and functional magnetic resonance imaging (fMRI), we sought changes in the topology of brain networks and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
0
16
2
Order By: Relevance
“…Among the various mathematical models, we need to select the appropriate one for the question to be addressed, e.g., graph-theoretical analysis, dynamic causal modeling, and computational modeling (Hartwigsen et al, 2013, Park et al, 2014, Cocchi et al, 2016). …”
Section: Tms-fmrimentioning
confidence: 99%
“…Among the various mathematical models, we need to select the appropriate one for the question to be addressed, e.g., graph-theoretical analysis, dynamic causal modeling, and computational modeling (Hartwigsen et al, 2013, Park et al, 2014, Cocchi et al, 2016). …”
Section: Tms-fmrimentioning
confidence: 99%
“…Resting-state functional MRI (rs-fMRI) measures spontaneous neuronal activity in human brain (Biswal et al, 1995) and has been commonly applied to explore the topological organization of brain functional networks (Wang et al, 2010). Park et al (2014) demonstrated that increased global efficiency and decreased local efficiency of the whole brain network was observed in participants who had greater motor performance changes after employing high-frequency rTMS (10 Hz) over the right M1. However, how different frequency rTMS over M1 modulates topological organization in the SMN remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Vecchio et al (2018) performed source localization on EEG data recorded before and after transcranial direct current stimulation (tDCS) and showed that anodal tDCS over the motor cortex reduces small-worldness. Park et al (2014), Polanía et al (2011), andCocchi et al (2015) studied the effects of various stimulation techniques using task fMRI and rs-fMRI data. Park observed a correlation between the motor performance change and the increase and decrease in global and local efficiency respectively, induced by 10 Hz rTMS (Park et al, 2014).…”
mentioning
confidence: 99%
“…Park et al (2014), Polanía et al (2011), andCocchi et al (2015) studied the effects of various stimulation techniques using task fMRI and rs-fMRI data. Park observed a correlation between the motor performance change and the increase and decrease in global and local efficiency respectively, induced by 10 Hz rTMS (Park et al, 2014).…”
mentioning
confidence: 99%